(untitled) (Journal of Engineering, 2011)
The capacity of Tigris River to transport the sediment within Al Mosul City is one of the most important characteristics of the river. Establishment of islands within this reach of the river because of decreasing the discharge of Tigris River can be controlled through studying this characteristic. Establishment of these islands and increase of the sediment deposition in the river reach affect the water treatment plants and the urban and industrial activities that are located on the banks of this reach. A steady one dimensional mathematical model for simulating the flow and estimating the sediment transport capacity of the studied reach was implemented and run by using the HEC-RAS (Version 3.1.3) software and making use of recorded field measurements for running and carrying out the calibration and verification processes. Flow velocity and sediment transport capacity were estimated for a range of discharge from 50 to 1500m3/sec. Locations of the low flow velocity were specified. The comparison between sediment capacity rating curves of these locations showed that the sediment transport capacity of the reach cross sections at 13000 and 4500m from the end of the reach, before and after Al Khosar River, is less than that of the other cross sections of this reach. The comparison between the sediment transport capacity and the inflow sediment quantity into the river reach before and after Al Khosar River with discharge and sediment concentration of 425m3/sec and 600ppm from Al Mosul Dam and 5m3/sec and 3150ppm from Al Khosar River showed that the deposited sediment in the river reach before and after Al Khosar River was 21900 and 15000tonnes/day, respectively. To avoid deposition of sediment before Al Khosar River and then along the studied reach the inflow discharge into the reach from Al Mosul Dam must be not less than 1500m3/sec. While, to avoid deposition of sediment after Al Khosar River the total discharge must be not less than 780m3/sec. The river reach cross section of low flow velocity must be developed to increase the sediment transport capacity.